EPR data hiding in MRI head volumes for telemedicine using rectangular box embedding method. (2018) - Kalaiselvi, T.; Somasundaram, K.; Vijayalakshmi, S.; Sriramakrishnan, P.
Mapping of electronic patient report (EPR) text file to magnetic resonance imaging (MRI) volumes increases burden to diagnosis over telemedicine. In this paper, we propose a high capacity, robust technique to select slices of interest (SOI) from a MRI volume that to embed EPR and transfer on a network. Embedding EPR along with selected slices is used to removal of mapping procedure at the receiver end. Initially brain extraction algorithm (BEA) is used to focus the region and ease of pathology detection in the slices. Then the embedding scheme uses the technique of rectangular box mapping (RBM) where it takes care of sensitive part of medical image. EPR data is encrypted and embedded for security purpose. Experimental results on security and robustness have been tested against various images. The proposed method can store longer EPR string along with better authenticity and confidentiality properties while satisfying all the requirements of medical data transfer and has achieved 51% reduction in bit rate than the traditional methods.